Study of Abundance and Fish Diversity in the Swamp Waters of Danau Bangkau, South Kalimantan - Ansyari, Pahmi; Ahmadi, Ahmadi; F. Ghanem, Sara (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2025)
The swampy waters of Danau Bangkau, South Kalimantan are swampy waters that have an economic impact on the surrounding community. There is a need for research to know the productivity status of these waters from the abundance and diversity of fish. The research was carried out by dividing into 3 fish sampling stations determined by purposive sampling. The fish samples obtained were identified from families and species. The parameters observed and analyzed included the relative abundance of fish, diversity index, Evenness index, and Dominance Index. The results of the study were obtained from 1,108 individual fish and 28 species from 10 families. The results of the study show that the largest relative abundance is from the Cyprinidae family, which is 56.14% and this indicates that the waters are quite healthy because many fish are inhabited by herbivorous eating properties. The Diversity Index (H') obtained was 2.53 – 2.71, Evenness Index 0.52 – 0.55 and Dominance Index 0.37 – 0.44 which means that the waters are still healthy, with moderate productivity, but tend to be somewhat disturbed. The implication is that in the future there must be protection of the swampy waters of Danau Bangkau with strategies to restrict fishing and control sedimentation and domestic pollution.